The impact of an active-learning designed faculty development program: A students' perspective of an Italian university - Monica Fedeli; Edward W. Taylor (Universidad de Deusto, 2023)
This study aims to understand the impact of a faculty development program emphasizing active learning (innovative teaching) attended by instructors of diverse disciplines at the University of Padova in Italy, which has had an 800-year history of using traditional approaches to teaching and learning. Using a community of practice theoretical framework, it recognized that the development of faculty learning communities provided a supportive medium for fostering innovative teaching. A multilevel research design involving surveys collected from 2019 to 2020 explored the program's impact in terms of student satisfaction and program effectiveness. Findings showed varied levels of impact, among student examination attempts, pass rates and average grades. These findings, although involving one university, are organizationally and culturally emblematic of other Italian universities and have related implications when considering the implementation of innovative approaches to teaching via faculty development programs. This study also revealed challenges (faculty engagement) and limitations when measuring (e.g., satisfaction, exam attempts) the impact of active learning in relationship to learning outcomes. Received: 30 June 2022 Accepted: 3 October 2023